Fatigue crack growth in welded S355 specimens subjected to combined loading - J. Lewandowski; D. Rozumek; Z. Marciniak; G. Lesiuk; R. Brighenti (Fracture and Structural Integrity)
The paper presents the results of experimental fatigue tests performed on welded S355 specimens subjected to combined bending and torsion loading. In order to analyse how the fillet joints shape and the load ratio affect the crack growth, we selected two kinds of fillet shape: concave and convex, and two load ratios, namely R = -1, 0. Rectangular specimens with stress concentrators in the form of the external two-sided blunt notches and fillet welded joint were tested. The test results were compared to experiments conducted on solid specimens without welds.